Educational practices as a component of the professional training of future geography teachers in foreign universities - Luniachek, V.; Borysenko, K.; Popov, V. (Problems of Engineer-Pedagogical Education, 2020)
This article highlights the features of practical training of future geography teachers in foreign universities, including the experience of the countries of the former Soviet Union, Germany, Great Britain and the USA. The conducted comparative analysis made it possible to formulate proposals for improving vocational training of specialists in this area in Ukraine. The work focuses on aspects of the formal training of a future geography teacher that are not adequately covered in the domestic scientific literature. Mainly, these are the algorithms for conducting educational practices in foreign universities, their meaningful content, venues and other components. It is proved that these approaches are quite diversified. This is especially true for universities in Western Europe and the USA. Similar changes are taking place in the post- Soviet countries that have become members of the European Union. But some countries that are part of the CIS use traditional higher education schemes of the Soviet Union period. The article separately notes the branching forms of educational practices for future geography teachers in universities in the UK and Germany. The study of this experience is extremely relevant in the context of the modernization of higher geographical education in Ukraine. For example, in universities of Great Britain, branching over narrow specialization in teacher training prevails. This fact significantly complicates the possibility of conducting specialized teaching practices and significantly affects the formation of individual special competencies of future geography teachers within the framework of the corresponding competency model. The authors also note that the experience of training future geography teachers in the United States is potentially useful for domestic specialists. It is distinguished by a significant number of curricula, organizational forms, orientation to the requirements of the education system of certain states and the like. The presented article is relevant to employees of both classical and pedagogical universities involved in the process of training a future geography teacher for institutions of general secondary education in Ukraine. The material presented is also useful for students who plan to continue their studies at foreign universities within the framework of mobility programs existing today.